BAHASA IBU DALAM PEMBELAJARAN ANAK DI SEKOLAH - Lisdwiana Kurniati, author (JURNAL PESONA, 2015)
Beside of gaining knowledge, the aim of learning in school is to make students be able to communicate (speech act) using the right Indonesian language in written and spoken, especially in classroom. However, teaching and learning process should use the mother tongue to make students can comprehend the material. Teacher should integrate communication with the context. First language facilitates students to speak and gain learning competences. That is why the term that mother tongue chaosing the use of Indonesian language can not be doctrinized.Keywords: Mother Tongue; Speech Act; Context.